Skimming and Scanning Strategies in Enhancing High School Students' Reading Skills by Using TOEFL Questions - Theodesia Lady Pratiwi; Jennifer Wiwit; Maya Marsevani (JL3T (Journal of Linguistics, Literature and Language Teaching), 2025)
This study examines the effectiveness of skimming and scanning strategies in enhancing students' TOEFL reading skills. Conducted through Classroom Action Research (CAR), the study involved 36 eleventh-grade students from a private high school in Batam. Participants were selected using a purposive sampling technique, assisted by the former teacher. The research was carried out in four stages: planning, action, observation, and reflection. A pre-test and a post-test were administered to evaluate student progress, along with field notes to document classroom observations. The effectiveness of the intervention was assessed by comparing the pre-test and post-test results. The findings revealed a statistically significant improvement in students' TOEFL reading comprehension. The average pre-test score increased from 69.47 to 82.23 in the post-test, which is classified as "very good" according to the scoring criteria. These results suggest that incorporating skimming and scanning strategies into TOEFL reading instruction significantly enhances comprehension skills. The study highlights the effectiveness of these strategies in improving students' reading abilities and overall TOEFL performance. Future research could explore the long-term effects of skimming and scanning strategies and compare them with other reading methods in TOEFL preparation.Reading Strategies; Scanning; Skimming; Toefl Reading.